PERILAKU MEROKOK PADA REMAJA PEREMPUAN - Lalangjaya Sinawang Surya; Doddy Hendro Wibowo (JISOS: JURNAL ILMU SOSIAL, 2023)
Adolescence is a period that is vulnerable to deviant behavior where one of them is smoking behavior. This study aims to determine the relationship between permissive parenting and smoking behavior in female adolescents. Participants used in this study were determined using techniquessnowball sampling, [d1]a total of 56 young girls aged 15-18 years. The results of this study indicate that there is a significant positive relationship between permissive parenting and smoking behavior with a correlation coefficient of r = 0.890 and a sig of 0.000 (p <0.05). This shows that there is a significant positive relationship between permissive parenting and smoking behavior in female adolescents